1983
DOI: 10.1128/jb.155.1.417-419.1983
|View full text |Cite
|
Sign up to set email alerts
|

Role of L-lysine-alpha-ketoglutarate aminotransferase in catabolism of lysine as a nitrogen source for Rhodotorula glutinis

Abstract: Wild-type and saccharopine dehydrogenaseless mutant strains of Rhodotorula glutinis grew in minimal medium containing lysine as the sole nitrogen source and simultaneously accumulated, in the culture supematant, large amounts of a product identified as a-aminoadipic-8-semialdehyde. The saccharopine dehydrogenase and pipecolic acid oxidase levels remained unchanged in wild-type cells grown in the presence of ammonium or lysine as the nitrogen source. Lysine-aketoglutarate aminotransferase activity was demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Considerable genetic and biochemical diversity also exist in yeasts and molds for the use of lysine as the sole nitrogen source. Distinct pathways for the use of lysine as the sole nitrogen source are used by Rhodotorula glutinis (KINZEL et al 1983), Saccharomycopsis lipolytica (GAILLARDIN et al 1976), Candida maltosa (SCHMIDT et al 1988) and Pichia guilliermondii (SCHMIDT et al 1987). Results presented in this report indicate that C .…”
Section: Homoisocitrate Dehydrogenase Glutamate-a-ketoadipate Transamentioning
confidence: 79%
See 1 more Smart Citation
“…Considerable genetic and biochemical diversity also exist in yeasts and molds for the use of lysine as the sole nitrogen source. Distinct pathways for the use of lysine as the sole nitrogen source are used by Rhodotorula glutinis (KINZEL et al 1983), Saccharomycopsis lipolytica (GAILLARDIN et al 1976), Candida maltosa (SCHMIDT et al 1988) and Pichia guilliermondii (SCHMIDT et al 1987). Results presented in this report indicate that C .…”
Section: Homoisocitrate Dehydrogenase Glutamate-a-ketoadipate Transamentioning
confidence: 79%
“…Minimal medium (MM) with ammonium sulfate as the sole nitrogen source consisted of glucose 10 g, DIFCO yeast nitrogen base without amino acids 6.7 g and distilled water to one liter. Medium with lysine or AA as the sole nitrogen source consisted of glucose log, DIFCO yeast nitrogen base without amino acids and ammonium sulfate 1.7 g (no nitrogen source; NN), L-lysine or DL-a-aminoadipate 2 to 5 g, distilled water to one liter (KINZEL et al 1983, WINSTON andBHATTACHARJEE 1982). Cultures were grown in small flasks or 150 mm x 18 mm test tubes in a 30 "C incubator shaker.…”
Section: Methodsmentioning
confidence: 99%
“…a-Aminoadipate-hemialdehyde could be produced in yeast by two different enzymes, lysine aminotransferase and lysine dehydrogenase. The aminotransferase of R. glutinis (KINZEL et al 1983) and of P. guiliiermondii (SCHMIDT et al 1987) was already characterized in detail, whereas we present here evidence for the occurrence of a novel amino acid dehydrogenase in both C. albicans and K , marxianus that catalyzes the oxidative deamination of the &-amino group of L-lysine. First studies showed that the lysine aminotransferase varied in its properties (e.g.…”
Section: Discussionmentioning
confidence: 55%
“…Investigations have shown that in some yeast species the latter two enzymic steps are used to catabolize L-lysine. In Rhodotorula glutinis (KINZEL et a/. 1983) and in Pichia guilliermondii (SCHMIDT et a/.…”
mentioning
confidence: 99%
“…In microorganisms, a-aminoadipate-8-semialdehyde (AASA) can be synthesized via three dif-Correspondence to" R. Bode, Ernst-Montz-Arndt-Umversltat Grelfswald, Sektlon Blolo~e, WB Molecularbiolog~e, Grelfswald 2200, G.D.R. ferent pathways: (i) as intermediate of the aaminoadipate pathway for the biosynthesis of lysine in lower eukaryotes catalyzed from aaminoadipate by the a-aminoadipate reductase [1]; (ii) in some yeasts [2,3] and some bacteria [4,5], lysine is catabolized as sole nitrogen source via a pathway in which AASA is formed from lysine by aminotransferase activity; and (iii) pipecolic acid can be converted in the presence of pipecolic acid oxidase to AASA by Pseudomonas species [6] and Rhodotorula glutmts [7].…”
Section: Introductionmentioning
confidence: 99%